PELATIHAN PENGELOLAAN KELAS BERBASIS PENDEKATAN DIFFERENTIATED LEARNING UNTUK GURU - M. Hafiz Sukri; Asna Wirayanti (PT. CASA CENDEKIA MEDIA, 2024)
Classroom management is one of the critical skills required to support effective teaching and learning processes. In the current educational context, differentiated learning has emerged as an essential approach to addressing the diverse needs of students in the classroom. This community service program aims to enhance teachers' competence in classroom management through training on differentiated learning strategies. The program involves interactive workshops, group discussions, and hands-on practices to equip teachers with the necessary skills to plan, implement, and evaluate classroom activities tailored to individual student needs. The training covers key aspects of differentiated learning, including curriculum adaptation, flexible grouping, and individualized instruction techniques. Participants are also introduced to tools and resources to design engaging and inclusive learning environments. The program is evaluated through pre-tests and post-tests to measure participants' understanding and confidence in applying differentiated learning strategies. Results indicate significant improvements in participants' knowledge and skills, with most teachers reporting increased confidence in managing diverse classroom dynamics effectively. This initiative highlights the importance of professional development programs in fostering innovative teaching practices. It is expected that the implementation of differentiated learning strategies will positively impact student engagement and achievement, contributing to the overall quality of education.